Bioaccessibility and biological activity of Melissa officinalis, Lavandula latifolia and Origanum vulgare extracts: influence of an in vitro gastrointestinal digestion - Gayoso, Lucía; Roxo, Mariana; Wink, Michael (Journal of functional foods, 2018)
Melissa officinalis, Lavandula latifolia and Origanum vulgare are widely used medicinal plants and spices. Their extracts were evaluated as potential antioxidants for functional food formulations. After being submitted to an in vitro gastrointestinal digestion, all the extracts showed antioxidant activity (measured by DPPH, ABTS, FRAP, TPC). Furthermore, their main polyphenols maintained high stability. Biological activity was measured using Caenorhabditis elegans, which is a widely used model in this context. Treatments of 50 and 100µg/mL of M. officinalis significantly attenuated juglone-induced stress in the survival assay performed; moreover, all tested concentrations decreased intracellular ROS. Lavandula latifolia and O. vulgare had no significant effect against acute stress in the survival assay, but significantly decreased ROS basal levels. GST-4 expression under juglone-induced oxidative stress was significantly down-regulated by treatment with the three plant extracts (up to 63%). Besides, similar biological activity of all digested extracts was demonstrated in all in vivo assays.
Gesehen am 12.09.2019